Effects Of Teaching And Learning Facilities And Lecturers’ Teaching Styles On Students’ Learning Motivation - Asep Candra Hidayat; Yunita Indriany; Nika Sintesa; Ela Laela (JURNAL MANAJEMEN PENDIDIKAN, 2026)
Learning motivation is a crucial factor in higher education as it determines students’ ability to absorb knowledge, develop skills, and achieve optimal academic performance. However, low learning motivation remains a persistent challenge in many higher education institutions, often influenced by inadequate teaching and learning facilities as well as less effective lecturers’ teaching styles. This study aims to examine the influence of teaching and learning facilities and lecturers’ teaching styles on students’ learning motivation at LP3I Jakarta Polytechnic, Depok Campus. A quantitative explanatory research design was employed, involving 81 students selected through stratified random sampling from a population of 425 students. Data were collected using questionnaires, observation, and documentation, and analyzed using descriptive statistics, multiple linear regression, correlation analysis, and hypothesis testing (t-test and F-test) with SPSS. The results reveal that teaching and learning facilities have a positive and moderate effect on students’ learning motivation, while lecturers’ teaching styles have a positive and strong effect. Simultaneously, both variables significantly influence students’ learning motivation, explaining 45.36% of the variance. These findings indicate that improving the quality of educational facilities and enhancing lecturers’ teaching styles are essential strategies for strengthening students’ learning motivation. Therefore, higher education institutions are encouraged to continuously upgrade learning facilities and support lecturers in developing more engaging, interactive, and student-centered teaching approaches to foster better learning motivation and academic outcomes.